Diagnostic heterogeneity in scrub typhus serology: A scoping review of IFA thresholds and regional standardisation needs (2005–2024) - Le, Khanh Kim; Saraswati, Kartika; Wongsantichon, Jantana; Day, Nicholas P. J.; Blacksell, Stuart D. (PLOS Neglected Tropical Diseases, 2025)
Author summary Scrub typhus is a serious disease caused by bacteria transmitted through the bites of infected mites. It is common in many parts of Asia and the Pacific. Diagnosing scrub typhus accurately is important for patient care and disease monitoring. Still, the most commonly used test—the indirect immunofluorescence assay (IFA)—varies widely in how it is used across different countries and laboratories. This review looked at nearly 20 years of published research to understand how other studies have used the IFA test. We found that there is no consistent agreement on what level of antibodies should count as a “positive” result, and many studies used different strains of the bacteria that may not reflect what is actually circulating in the region. These differences make it hard to compare results across countries or over time. The findings show a clear need for more consistent, regionally appropriate guidelines on how to perform and interpret this test. Improving standardisation will help ensure more accurate diagnoses, better tracking of disease patterns, and stronger public health responses in areas where scrub typhus is common.